2009
DOI: 10.1016/j.metabol.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of food versus protein restriction on selected nutritional and inflammatory markers in rats

Abstract: We previously demonstrated that feeding a 2% protein AIN-76 diet ad libitum for 14 days resulted in substantial clinical and biochemical changes including weight loss, hypoglycemia, hypoalbuminemia, higher levels of plasma cytokines, oxidative stress in the liver, and activation of inflammatory signaling to interleukin (IL)-6, as compared with a 20% protein diet. In the present study, 54 rats were randomly given a standard rat chow diet ad libitum, or a 25% or 50% reduction of this intake for 14 days. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
(36 reference statements)
1
19
0
6
Order By: Relevance
“…Similar to our results, Chacón and co-workers reported increased plasma corticosterone level in rats after 4 weeks receiving 66% of recommended caloric needs (Chacón et al 2005). Increased plasma corticosterone level was also reported in rats whose food intake during 14 days was reduced for 25% and 50%, comparing to control group (Ling and Bistrian 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, Chacón and co-workers reported increased plasma corticosterone level in rats after 4 weeks receiving 66% of recommended caloric needs (Chacón et al 2005). Increased plasma corticosterone level was also reported in rats whose food intake during 14 days was reduced for 25% and 50%, comparing to control group (Ling and Bistrian 2009).…”
Section: Discussionsupporting
confidence: 91%
“…In both animal and human studies, a protein‐restricted diet impairs both cell‐mediated and humoral immunity 31 , 32 . Moreover, dietary protein restriction produces a pro‐inflammatory state (increase in IL‐1, IL‐6, and TNF‐α) that is interestingly not seen with caloric restriction alone 33 . As protein intake is a potentially modifiable prognostic factor, these findings support the performance of prospective randomized trials in the area.…”
Section: Discussionmentioning
confidence: 62%
“…However, the pair-fed sham-operated rats that were controlled in order that they would consume the same amount of food as that consumed by GERD rats showed plasma ghrelin levels similar to those in shamoperated rats. It has been reported that plasma ghrelin levels in rats with food intake restricted by 25% and 50% that were measured 15 days after the initiation of restriction did not differ from rats with ad libitum food intake (27). Therefore, it has been suggested that the increased plasma ghrelin levels in GERD rats may have not resulted solely from reduced food intake.…”
Section: Discussionmentioning
confidence: 95%